Digital Savvy: Know the Technology, Be Aware of the Dangers - Feri Alpiyasin; Hasanah Tisna Amijaya; Ganjar Nurul Fajar; Jajat Sudrajat; Muhamad Firza; Putri Alivia Nur Khalizah; Trisna Saputra; Naia Aulia Fitria; Angel Savira Pricillia Pratama; Thazkia Listi Alistianti; Alya Nazhara Nurseptia; Moch Rival Mulyadi; Ghaida Nafisyah; Syahril Fathan Sailendani; Allya Azkya Subarja; Elsa Wirda Saputra (LPPM STMIK Mardira Indonesia, 2025)
The community service initiative titled